Peningkatan Ekonomi Masyarakat Melalui Pelatihan Pembuatan Produk Egg Roll Frozen Berbahan Daging Ikan - Wibowo, Larasati Sukmadewi; Nento, Wila Rumina; Bakari, Yuliana (Universitas Negeri Gorontalo, 2023)
The social activities service by the student of KKN Tematik program, aim to provide education and direct training to the community regarding the process of making frozen skipjack egg rolls which can provide business opportunities to the community in Buhudaa Village, Batudaa Pantai District, especially housewives as home-based businesses. highly nutritious. The activity location is in the village of Buhudaa, Batudaa Pantai District. Making egg rolls can be used as an additional effort that is very useful and has economic value and is very popular with all walks of life. Based on the results of the activities and training, the community has high enthusiasm for making egg rolls because the manufacturing process is relatively easy and the availability of raw materials is abundant in the village. The BEP value is 85.79 packs per 90 grams, that the frozen egg rolls business will break even when selling 86 packs, with a price per pack of Rp. 20,000.00 the community will get added value and a profit of Rp. 282,200.00. Improving the Community's Economy through Training on Making Frozen Egg Roll Products Made from Fish MeatAbstract: The social activities service by the student of KKN Tematik program, aim to provide education and direct training to the community regarding the process of making frozen skipjack egg rolls which can provide business opportunities to the community in Buhudaa Village, Batudaa Pantai District, especially housewives as home-based businesses. highly nutritious. The activity location is in the village of Buhudaa, Batudaa Pantai District. Making egg rolls can be used as an additional effort that is very useful and has economic value and is very popular with all walks of life. Based on the results of the activities and training, the community has high enthusiasm for making egg rolls because the manufacturing process is relatively easy and the availability of raw materials is abundant in the village. The BEP value is 85.79 packs per 90 grams, that the frozen egg rolls business will break even when selling 86 packs, with a price per pack of Rp. 20,000.00 the community will get added value and a profit of Rp. 282,200.00.